Transvaginal two-dimensional ultrasound measurement of cervical volume to predict the outcome of the induction of labour: a prospective observational study - S. R. Athulathmudali; M. Patabendige; S. K. Chandrasinghe; P. H. P. De Silva (BMC, 2021)
Abstract Background Assessing the likelihood of success of induction of labour using ultrasonically measured cervical volume is an important research question. Method A prospective observational study was carried out at North Colombo Teaching Hospital, Ragama, Sri Lanka. Pre-induction digital cervical assessment, transvaginal cervical length, and cervical volume measurements were performed. Inductions with singleton pregnancies at term were included. Basic demographic and clinical details, independent variables (Bishop score, cervical length and cervical volume), and dependent variables (frequency of delivery within 24 h and induction to delivery interval) were recorded. Vaginal delivery within 24 h was the primary outcome. Results We studied 100 pregnant women who had induction of labour. Median (IQR) Bishop score was 5 (3-6), mean (SD) cervical length was 3.6 (0.7) cm, and mean (SD) cervical volume was 27.5 (10.4) cm3. Cervical length was the best predictor for predicting the likelihood of vaginal delivery within 24 h [aOR - 12.12 (3.44, 42.71); < 0.001], and cervical volume also appeared to be a significant potential predictor [aOR-1.10 (1.01, 1.17); 0.01]. Cervical length was found to have the highest AUC (0.83) followed by the cervical volume (0.74). The best cut-off value for cervical volume in predicting the likelihood of vaginal delivery within 24 h was less than 28.5 cm3 with a sensitivity of 72% and specificity of 74%. Conclusions Transvaginal sonographic measurement of cervical volume appears to be a potential novel predictor for the likelihood of vaginal delivery within 24 h of induction of labour. Cervical length is still more superior to cervical volume in predicting the likelihood of vaginal delivery. Bishop score was not a significant predictor in this context.